Contagion And Firms' Internationalization In Latin America : Evidence From Mexico, Brazil, And Chile - Sakho, Yaye Seynabou (The World Bank, 2006)
The author investigates whether contagion matters when emerging market firms cross-list their stocks in a developed capital market. She develops a rational expectations model where financial markets are segmented along emerging markets' borders and contagion spreads from one emerging market to another through the actions of international investors rebalancing their portfolio using stocks cross-listed in the developed market. The author finds that contagion is a cost of internationalization as cross-listed stocks are more affected by contagion than pure domestic stocks. Furthermore, a welfare analysis of international cross-listing versus financial autarky suggests that the benefits of internationalization in terms of less information asymmetry and better market efficiency offset the costs of contagion. Her model is able to explain some transmission of the 1998 Brazilian crisis to Mexico and Chile